Effects of small-sided games and high-intensity interval training on physical performance in young female handball players - Vukadinović Jurišić, Mila; Jakšić, Damjan; Trajković, Nebojša; Rakonjac, Dušan; Peulić, Jovica; Obradović, Jelena (Biology of Sport, 2021)
This study was designed to compare the effectiveness of small-sided handball games in combination with handball training (SSG group) versus high-intensity interval training in combination with handball training (HIIT group) on physical performance of young female handball players during pre-competitive period. Twentyfour young female handball players, who have a 6.17 ± 1.54 years training experience and competition in the national league participated in this study. SSG group (n = 12; age 16.06 ± 0.80 years, body mass 61.27 ± 3.68 kg, body height 1.64 ± 4.7 m, body mass index 22.7 kg/m2 ) while HIIT group (n = 12; 16.20 ± 1.28 years, body mass 62.46 ± 7.86 kg, body height 1.68 ± 6.8 m, body mass index 22 kg/m2 ). Both groups applied training programs twice-a-week for 8 weeks. Before and after the training programs physical performances were assessed: Countermovement jump (CMJ), Squat jump (SJ), Sprint on 0–10 m; Sprint on 0–20 m; Sprint on 0–30 m, Throwing medicine ball and total distance covered during the Yo-YoIRT1. After 8 weeks SSG and HIIT groups significantly improved CMJ, SJ, 0–20 m sprint, 0–30 m sprint, throwing medicine ball and Yo-YoIRT1 (p ≤ 0.05). However, significantly greater improvement was achieved in Yo-YoIRT1 (m) in HIIT group (28.40%) than SSG group (17.63%). These results indicate that SSG group and HIIT group equally improve of physical performances (jump, sprint and upper explosive strength) among young female handball players in pre-competitive period.